Transformasi Identitas Budaya Minangkabau di Perantauan - Azura, Kyla Puteri; Millah, Salma Auzia Minhatul; Chairunissa, Jesenia; Visidia, Lisa Cosmona (TSAQOFAH, 2024)
The Minangkabau people, often called Minang, are an ethnic group primarily living in the province of West Sumatra, Indonesia. With the rapid pace of globalization and urbanization, many Minangkabau people choose to migrate in search of better economic opportunities and quality of life. Merantau, or migration, has become a widespread tradition in the Minang community. Traditionally, this practice was carried out by men, while women stayed in their hometowns. However, nowadays, women also participate in merantau. Migration is not only a part of a long-standing tradition passed down through generations but also a way to demonstrate personal maturity and responsibility. The spirit of merantau is very strong among the Minangkabau people, with surveys suggesting that their migration rate is among the highest in Indonesia. This migration process encourages cultural acculturation, which can either strengthen or alter the original Minangkabau culture. With increasing education levels and broader perspectives, many Minangkabau people are beginning to question the matrilineal kinship system that has traditionally defined their society. While these changes can bring positive effects, they also carry the risk of altering or diluting long-held customary values.